Strategy Preschool Teachers’ Experiences in Handling Early Childhood Children with Indications of Speech Delay - Handayani, Lisya; Fridani, Lara; Rahayu, Wardani (Universitas Nahdlatul Ulama Surabaya, 2023)
Dealing with these situations, educators must approach them with sensitivity and take the right steps to handle them. The purpose of this study is to determine the role of the teacher and the strategies they use in handling children with speech delays. The subjects of this study were preschool teachers who directly worked with such children. The data was collected through interviews and observations. The qualitative data showed that participants faced various challenges. The researcher concluded that the teacher's role is to create a conducive learning environment, encourage children to participate actively in activities, facilitate children to interact and cooperate in small groups, make learning plans, conduct continuous assessments, and create reports on children's individual development and learning. Teachers should use various learning methods, educational media, and provide positive feedback to students..